A Family with An Overlap Of Acropigmentation Of Kitamura And Dowling Degos Disease - Sethuraman G; Thappa Devinder Mohan; Singh Sirisha; Rao Ramachandra K (Wolters Kluwer Medknow Publications, 1999)
Reticulate acral and flexural pigmentary disorders are a rare group of pigmentary genodermatoses. We report a family showing a combination of features described in the two disorders; reticulate acropigmentation of kitamura (RAPK) and Dowling Degos disease, along with palmoplantar keratoderma. We speculate that RAPK and DD are part of a spectrum of reticulate pigmentary disorders with varied phenotypic expression.